Penerapan Model Pembelajaran Cooperative Learning Tipe Make A Match untuk Meningkatkan Keaktifan dan Hasil Belajar pada Mata Pelajaran Produk Kreatif dan Kewirausahaan (Penelitian Tindakan pada Kelas XI Bisnis Daring dan Pemasaran SMK N 3 Surakarta Tahun - diah novitasari; Bambang Wasito Adi; sudarno sudarno (BISE: Jurnal Pendidikan Bisnis dan Ekonomi, 2022)
This study aim to prove whether the application of the cooperative learning model with the make a match type in the subject of creative products and entrepreneurship can improve the activeness and learning result of Class XI students of SMK N 3 Surakarta in the academic year 2019/2020. This research method is a Classroom Action Research (CAR) conducted in 2 cycles. Each cycle consists of 4 steps which are planning, implementing actions, observing and reflecting. The subjects of this study were 35 students of class XI PM 3 SMK N 3 Surakarta. The instruments in this study were active learning observation sheets and learning achievement tests.The results showed that there was an increase in activeness that can be seen from the percentage of learning activeness in pre-cycle of 48.56% increasing to 71.42% in the first cycle, then in the second cycle increasing to 88.56%. In conclusion, student learning activeness has increased by 40%. Cognitive aspects of learning outcomes increased with the acquisition of pre-cycle data achievement of 45.71% increased in the first cycle to 71.42% and increased again in the second cycle to 85.71%. Affective aspects of learning outcomes with pre-cycle data acquisition achievement of 58.33% increased in the first cycle to 79.99% then increased again in the second cycle to 86.63%. Psychomotor aspects of learning outcomes with pre-cycle data acquisition achievement of 47.63% increased in the first cycle to 79.04% then in the second cycle increased to 86.63%. Based on these results it can be concluded that the application of cooperative learning model make a match type can improve student activeness and learning result in the subject of Creative Products and Entrepreneurship in Class XI Marketing at SMK N 3 Surakarta in the 2019/2020 academic year.